Directed generosity and network formation: Network dimension matters - Ben D'Exelle; Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2010)
We explore network effects on generosity for different network dimensions. To this end we elicit multiple network dimensions (friendship, social support, economic exchange, etc.) in a rural village in the Southern hemisphere and measure generosity with a sequence of dictator games conducted in the field. We find that networks of different dimensions differ substantially in density, clustering, and centrality. When relating generosity to networks we observe that social distance only matters for friendship ties but that structural network variables are important in all network dimensions. Importantly, these effects are not invariant across different network dimensions. We also find that individual characteristics are unrelated with generosity per se but that they have strong explanatory power for network formation.
Keywords: C72; C90; D64; L14; Z13; 330; networks; generosity; network formation; experiments; Soziales Netzwerk; Nichtkooperatives Spiel; Test